Pengembangan Potensi Desa Wisata Buayan Kecamatan Buayan Kabupaten Kebumen melalui Media Sosial - Eka Ferani Dewi Purwanti; Wiludjeng Roessali (Jurnal Pengabdian KOLABORATIF, 2023)
Community Service Program (KKN) is the real evidence of the implementation of the Tri Dharma of Higher Education, namely in the aspect of community service. Through KKN activities in Buayan Village, it is hoped that there will be synergy between universities and the community as a form of community empowerment towards a post-Covid-19 pandemic based on Sustainable Development Goals (SDGs). The purpose of this activity is to help increase the understanding and ability of Bina Sejahtera Buayan village-owned enterprise (BUMDes) managers in promoting the potential of tourism villages through social media. In addition, this activity is also expected to expand the promotion of top products of the village so that they can support village tourism and increase the village s original income (PADes). Community service activities based on the KKN work program are carried out offline by providing digital branding training to village officials and BUMDes managers in promoting and publicizing the tourism potential of Langen Ujung Baths in Buayan Village, Buayan District, Kebumen Regency. In addition, visits and assistance are also carried out to promote UMKM products through social media to support the existence of this tourist village.